Type the correct answer in each box. Use numerals.
1 answer:
2y=-x+9
6y=3(-x+9)
3x-3(-x+9)=-15
3x-(-3x+27)=-15
3x+3x-27=-15
6x=-15+27
6x=12
x=2
2y=-2+9
2y=7
y=7/2
Answer is (2 ; 7/2)
You might be interested in
Answer:
56 + 24 = 80
56 X 100 = 5600
5600/80 = 70%
Hello,
Answer A
s(x)=3x-7
s(2t-4)=3*(2t-4)-7=6t-12-7=6t-19
Answer:
b
B zero product property
Answer:
No.
Step-by-step explanation:
The Triangle Inequality Theorem states that this is not possible.
Answer:dwqdwdqw
Step-by-step explanation:
abuhchqecieuc